Visual art teachers’ determination of the self sufficiency to use alternative assessment tools - Sehran Dilmaç; Oğuz Dilmaç (Institute of Advanced Engineering and Science, 2020)
The aim of this study was to examine visual arts teachers’ opinions on determination and evaluation of self-efficacy beliefs concerning using to alternative assessment tools. In this study ‘the survey research model’ from descriptive research was used in which the aim was to determine the opinions of visual arts teachers about the alternative assessment evaluation. A descriptive survey model was used as the quantitative research method. Data was obtained through a Likert scale that is also named as ‘Progression File, Performance Assessment and using the Grading Key Sufficiency Scale by the Visual Arts Teachers’. The study is conducted with 123 visual art teachers in the Turkey in the 2018-2019 academic years. Progression File, Performance Assessment and using the Grading Key Sufficiency Scale was applied to Visual Arts Teachers. It was determined that most of the teachers found themselves adequate about the evaluation process.